Dimensionando o programa Bolsa Família - Ricardo Barros; Mirela de Carvalho; Rosane Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This study aims to propose principles that are fully compatible with the historical evolution of the Bolsa Família program and with its current dimension. These principles provide the size of the population to be served and the magnitude of benefits to be granted for any scenario of growth in per capita income, with or without a change in the degree of inequality. To operationalize these principles, however, it was necessary to establish, first, what is the typical degree of inequality for countries with per capita income similar to Brazil. The proposed procedure allowed the identification, according to the standard for countries with similar per capita income, which should be the percentage of income earned by the poorest 10% and the second tenth. We defined thus a gap of inequality to be reduced by the Bolsa Família program.
Keywords: I30; I32; I38; 330